Blogging as a means to develop entrepreneurial attitudes in students of an agricultural technical and professional high school. - Cóndor Lazo, Noemí Ana María (2022)
The attitudinal component is an aspect to be evaluated and improved, as well as to include strategic methodologies considering connectivism. The research objective proposes to contrast the incidence of the use of the blog as a means to develop entrepreneurial attitudes in students of the 4th grade level of the Liceo Agrícola Técnico Profesional Padre Francisco Napolitano de Lluta - Arica - Chile 2018. A pre-experimental design was used, of inferential analysis. Through the surveys, a validated and reliable questionnaire was administered to a sample of 21 students from the institution. The conclusions of the research report with a statistical certainty of 95%, that the relationship between blog use and entrepreneurial attitudes improve with a range of 22% in students, Likewise the level of achievement by attitudinal components gives the following results. In the cognitive component with 57.1% it rises to a high level and with 42.9% it rises to a very high attitude level, in the affective component: 38.1% high attitude and 61.9% very high attitude. In the behavioral component, a high (52.4%) and very high (47.6%) attitude is observed. The analyzed information was delivered to the direction of the institution to consider in future activities, consider an interconnected, dynamic world, thus continue to improve and implement methodological strategies in teaching - learning centered on students, considering their special conditions